PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XII PEMINATAN MIPA SMAN 4 SUNGAI PENUH - Hutauruk, Tetty Ronauli (Departemen Matematika, 2024)
By comparing the effectiveness of the Discovery Learning model with a more traditional learning model, this study hopes to identify gaps in learners' understanding of mathematical concepts. Those enrolled in class XII MIPA at SMAN 4 Sungai Penuh in the 2024-2025 school year will be the main subject of this research. This research is a quasi-experiment. Four groups of learners from class XII MIPA SMAN 4 Sungai Penuh became the research population. There are 35 students in the experimental class (XII A) and control class (XII D). To collect data for this study, we gave the participants a final test to measure how well they understood the math concepts. After that, t-test was used to test the collected data. Based on the analysis, the P-value was 0.034, which is lower than α. Therefore, those who used the Discovery Learning model to acquire math concepts outperformed their peers who used more traditional learning methods.Keywords– Discovery Learning, Mathematical concept understanding